A high-temperature-resistant laminated busbar plate assembly and a preparation method thereof
Patent Information
- Application Number
- CN202611125233.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-09-29
- Estimated Expiration
- 2046-07-28
AI Technical Summary
该类结构在常规工况下能够满足基本导电和绝缘需求,但在高温及冷热交变环境中,导电基层、表面金属镀层、粘接层和绝缘膜之间的界面性质差异会逐渐放大
[0025]与现有技术相比,本发明的有益效果为:本发明的耐高温叠层母排极板组件通过优化镀锡导电基层与聚酰亚胺绝缘膜之间的粘接体系,实现了在高温及冷热循环条件下层间结合的稳定性。镀锡侧粘接层中巯基硅烷偶联剂通过水解缩合在金属表面形成硅氧锡键和硅氧硅网络,并与环氧树脂形成互穿连续相,增强了金属界面锚定能力;PI侧粘接层中的耐热环氧树脂、苯氧树脂及双端环氧聚二甲基硅氧烷在芳香胺固化剂和咪唑促进剂作用下形成高度交联的环氧固化网络,并通过分散相结构与PI膜表面极性基团产生氢键和偶极作用,形成连续的化学及物理界面结合。该结构在压合和熟化过程中产生的微相分离和链段取向调节了界面应力分布,使层间剥离和翘曲被限制。由此,本发明的组件能够在宽温域运行中保持导电层与绝缘层的界面结合力和绝缘性能,改善叠层母排的结构可靠性和长期稳定性,同时降低界面缺陷风险,提高设备在苛刻工况下的安全性和可靠性。
Smart Images

Figure CN122638235B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of stacked busbar electrical connection components, and relates to a high-temperature resistant stacked busbar electrode plate assembly and its preparation method. Background Technology
[0002] Laminated busbars are crucial components in power electronic equipment used for power circuit connections. They are typically formed by laminating and pressing together conductive electrode plates, insulating films, and interlayer adhesives. Compared to traditional cable connections, laminated busbars offer advantages such as lower circuit inductance, more compact structure, and better assembly consistency, making them widely used in frequency converters, inverters, energy storage converters, SVG equipment, and other high-power power electronic devices. As equipment power density increases, the heat load and temperature fluctuations experienced by busbar assemblies during operation gradually increase, placing higher demands on their interlayer adhesive stability, insulation reliability, and dimensional stability.
[0003] Existing multilayer busbar electrode assemblies typically use copper busbars or surface-metallized copper busbars as the conductive base layer, with a polymer insulating film on the outside of the conductive base layer. The layers are bonded together using ordinary epoxy adhesives or heat-resistant resin adhesives. This type of structure can meet basic conductivity and insulation requirements under normal operating conditions. However, in high-temperature and alternating thermal environments, the differences in interfacial properties between the conductive base layer, the surface metal plating, the adhesive layers, and the insulating film gradually amplify. Especially between the tin-plated conductive base layer and the PI (polyimide) insulating film, ordinary adhesive layers often struggle to simultaneously ensure metal-side interfacial bonding, PI-side interfacial adhesion, and stress buffering during thermal cycling.
[0004] Therefore, the technical problem to be solved by the present invention is: how to design an interlayer bonding system that can maintain stable adhesion and insulation performance between the tin-plated conductive substrate and the PI insulating film under high temperature and alternating hot and cold conditions. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a high-temperature resistant multilayer busbar electrode assembly and its preparation method. This is achieved by forming a tin-plated adhesive layer comprising γ-mercaptopropyltrimethoxysilane and epoxy resin on the conductive substrate surface, and an adhesive layer comprising epoxy, double-ended epoxy-terminated polydimethylsiloxane, and phenoxy resin on the PI insulating film side, thus realizing a continuous interfacial bond between the tin-plated layer and the PI film. This method, through the design of end-reinforcing blocks and composite adhesive layers, controls interlayer thermal expansion matching, alleviates interfacial stress, and achieves interfacial stability, peel strength maintenance, insulation performance, and warpage control under high temperature and thermal cycling conditions. Simultaneously, it ensures the feasibility of the fabrication process and the uniformity and continuity of the interlayer structure.
[0006] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a high-temperature resistant multilayer busbar electrode assembly, comprising a conductive base layer, a tin-plated layer, a high-temperature resistant composite adhesive layer, a PI insulating film, and an FR-4 insulating fixing block; The tin plating layer is disposed on the surface of the conductive substrate; the high-temperature resistant composite adhesive layer is disposed between the tin plating layer and the PI insulating film; The high-temperature resistant composite adhesive layer includes a tin-plated side adhesive layer in contact with the tin-plated layer and a PI-side adhesive layer in contact with the PI insulating film; the tin-plated side adhesive layer includes γ-mercaptopropyltrimethoxysilane and epoxy resin. The PI-side adhesive layer includes heat-resistant epoxy resin, phenoxy resin, double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, aromatic amine curing agent and imidazole curing accelerator. The side of the PI insulating film facing the high-temperature resistant composite adhesive layer is a roughened surface or a corona-treated surface. The FR-4 insulating fixing block is disposed at the end of the stacked structure formed by the conductive base layer, the tin-plated layer, the high-temperature resistant composite adhesive layer and the PI insulating film.
[0007] Preferably, the conductive base layer is a T2 copper plate, the thickness of the conductive base layer is 1.5-3.0 mm, the thickness of the tin plating layer is 5-8 μm, and the edges of the conductive base layer are provided with a rounded corner passivation structure.
[0008] Preferably, the thickness of the PI insulating film is 0.05 mm.
[0009] Preferably, the thickness of the tin-plated side adhesive layer is 1-3 μm, and the thickness of the PI side adhesive layer is 25-35 μm.
[0010] Preferably, the epoxy resin is one or both of bisphenol A type epoxy resin and bisphenol F type epoxy resin, and the epoxy equivalent of the epoxy resin is 170-250 g / eq.
[0011] Preferably, in the tin-plated adhesive layer, the mass ratio of γ-mercaptopropyltrimethoxysilane to the epoxy resin is (0.5-2):1.
[0012] Preferably, in the PI side adhesive layer, the mass ratio of the heat-resistant epoxy resin, the phenoxy resin, the double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, the aromatic amine curing agent and the imidazole curing accelerator is 100:(5-20):(2-8):(20-40):(0.3-1.5).
[0013] Preferably, the heat-resistant epoxy resin is one or more of phenolic epoxy resin, biphenyl epoxy resin, and multifunctional epoxy resin; the weight-average molecular weight of the phenoxy resin is 40,000-45,000; the number-average molecular weight of the double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane is 800-2,000; the aromatic amine curing agent is one or two of 4,4'-diaminodiphenylmethane and m-phenylenediamine; and the imidazole curing accelerator is one or more of 2-ethyl-4-methylimidazolium, 2-methylimidazolium, and 2-phenylimidazolium.
[0014] Preferably, the PI side adhesive layer further includes sheet-like insulating filler, which is one or more of sheet-like boron nitride, sericite, and sheet-like talc; the mass ratio of the heat-resistant epoxy resin to the sheet-like insulating filler is 100:(1-8), the average sheet diameter of the sheet-like insulating filler is not greater than 5μm, the maximum sheet diameter is not greater than 8μm, and the aspect ratio is not less than 10.
[0015] In a second aspect, the present invention provides a method for preparing the high-temperature resistant laminated busbar electrode assembly described in the first aspect, comprising the following steps: S1, the conductive substrate is subjected to surface tin plating to form a tin plating layer, and the edges of the conductive substrate are rounded and passivated. S2, mix γ-mercaptopropyltrimethoxysilane, epoxy resin and organic solvent to obtain tin-plated side adhesive liquid, coat the tin-plated side adhesive liquid onto the surface of the tin-plated layer and dry it to obtain a base coating substrate; S3, heat-resistant epoxy resin and phenoxy resin are mixed and heated to dissolve. After cooling, double-ended epoxypropoxypropyl-terminated polydimethylsiloxane, aromatic amine curing agent and imidazole curing accelerator are added. After mixing, PI side adhesive is obtained. The PI side adhesive is coated on the tin-plated side adhesive layer surface of the base coating substrate to obtain the adhesive-coated substrate. S4, after the roughened surface or corona-treated surface of the PI insulating film comes into contact with the PI side adhesive of the coated substrate, it is pressed and cured to obtain a laminated structure. S5, FR-4 insulating fixing blocks are provided at the ends of the stacked structure to obtain a high-temperature resistant stacked busbar electrode assembly.
[0016] Preferably, in step S2, the organic solvent is one or more of ethanol, isopropanol, and acetone, and the water content of the organic solvent is 0.1-1.0 wt.%; the mixing time is 20-60 min; the drying includes a first drying section and a second drying section, the temperature of the first drying section is 70-90℃ and the time is 3-8 min, and the temperature of the second drying section is 100-110℃ and the time is 1-5 min.
[0017] Preferably, in step S3, the temperature at which the heat-resistant epoxy resin and the phenoxy resin are mixed and heated to dissolve is 120-140°C for 60-120 minutes; the temperature after cooling is 90-95°C; the mixing time after adding the double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, aromatic amine curing agent, and imidazole curing accelerator is 20-60 minutes; and vacuum degassing is performed after mixing for 5-20 minutes.
[0018] Preferably, in step S4, the pressing temperature is 175-195℃, and the molding pressure is 100 kg / cm². 2 The molding time for single-sided panels is 60-120s, and the molding time for double-sided panels is 120-180s. The curing conditions are 160℃ for 60min.
[0019] In air, the tin-plated layer forms an interface layer mainly composed of tin oxide and surface hydroxyl groups. γ-mercaptopropyltrimethoxysilane undergoes alkoxy hydrolysis in an organic solvent containing a small amount of water, generating silanol structures. These silanol structures condense with the hydroxyl groups on the tin-plated layer surface, forming siloxane-tin bonds; some silanols also undergo self-condensation, forming siloxane-silicon structures. The thiol groups, located at the other end of the silane molecule, can coordinate with the tin surface, resulting in a thin layer on the tin-plated side adhesive layer containing siloxane-tin, siloxane-silicon, and thiol interfacial interaction sites. Epoxy resin is distributed within this thin layer, providing a continuous organic phase and reducing the brittleness of the pure silane condensation layer. During subsequent pressing and curing, aromatic amine curing agents and imidazole curing accelerators in the PI-side adhesive layer diffuse to the tin-plated side adhesive layer interface, participating in the ring-opening curing of the epoxy resin, thus forming a continuous epoxy curing network between the tin-plated side adhesive layer and the PI-side adhesive layer.
[0020] After roughening or corona treatment, the PI insulating film develops a micro-uneven structure on its surface, introducing oxygen-containing polar groups such as hydroxyl, carboxyl, and carbonyl groups. During lamination, the PI side adhesive penetrates the micro-recessed regions of the roughened surface, forming a mechanical interlocking effect after curing. Simultaneously, hydrogen bonds, dipole interactions, and inter-aromatic interactions are formed between the hydroxyl, ether, and aromatic structures in the epoxy curing network and the imide structures and oxygen-containing polar groups on the PI surface. This interfacial interaction ensures that the bonding between the PI insulating film and the PI side adhesive layer relies not only on surface wetting but also on the interaction between the cured resin network and the polar groups on the PI surface.
[0021] In the PI-side adhesive layer, the heat-resistant epoxy resin undergoes an epoxy ring-opening addition reaction with an aromatic amine curing agent. The active hydrogen in the aromatic amine attacks the epoxy group, opening the epoxy ring and generating a hydroxyl group. The resulting secondary amine then continues to react with the epoxy group, forming a cross-linked network containing hydroxyl groups, ether bonds, and aromatic structures. Imidazole curing accelerators can form active intermediates with the epoxy groups, promoting the ring-opening and chain growth reactions, allowing the curing reaction to proceed under compression and aging conditions. The cross-linked network formed after curing serves as the continuous phase of the PI-side adhesive layer, providing structural support and a heat-resistant framework.
[0022] Phenoxy resin contains aromatic rings, ether bonds, and hydroxyl groups in its molecular chain. When dispersed in heat-resistant epoxy resin under heating conditions, it does not act as a major crosslinking component after compression curing. The hydroxyl groups on the phenoxy resin molecular chain can form hydrogen bonds with the hydroxyl groups, ether bonds, and polar groups on the PI film surface in the epoxy curing network. Its aromatic ring structure can improve the interfacial compatibility with the PI molecular chain. The linear segments of phenoxy resin are beneficial for improving the film-forming continuity of thin adhesive layers, and under external force, it absorbs some deformation energy through segment orientation and interfacial hydrogen bond rearrangement, reducing local stress concentration in the epoxy curing network.
[0023] Bis-terminated epoxypropyl-terminated polydimethylsiloxane molecules contain epoxy groups at both ends and polydimethylsiloxane segments in the middle. In PI-side adhesives, its end-epoxy structures participate in the aromatic amine curing reaction and enter the curing network together with the heat-resistant epoxy resin. The polydimethylsiloxane segments do not exist as free plasticizers but are incorporated into the epoxy crosslinking structure through end-group reactions. Due to the limited compatibility between the polydimethylsiloxane segments and the epoxy resin matrix, microphase separation occurs during curing, forming a structure with the epoxy curing network as the continuous phase and the polydimethylsiloxane segment-rich regions as the dispersed phase. The dispersed phase size is affected by the molecular weight of the polydimethylsiloxane, mixing conditions, and curing rate. When using lower molecular weight bi-terminated epoxy polydimethylsiloxanes, the segment length is limited, the end-group reaction ratio is increased, and the dispersed phase size is restricted, avoiding the formation of continuous defect channels in thin adhesive layers.
[0024] During the alternating hot and cold cycles, differences in thermal deformation exist between the conductive substrate, the tin plating layer, the PI insulating film, and the adhesive layer. The epoxy curing network provides a continuous framework for the adhesive layer. Under localized stress, phenoxy resin segments and polydimethylsiloxane segments grafted into the network undergo segment orientation, dispersed phase deformation, and interfacial energy dissipation. The siloxane-tin interface structure and the coordination effect of mercapto groups on the tin surface in the tin-plated adhesive layer restrict the adhesive layer from peeling off from the tin-plated interface. The mechanical interlocking and polar interaction between the PI-side adhesive layer and the PI film restrict the adhesive layer from peeling off from the PI-side interface. The thin-layer structure formed during lamination ensures full contact between the tin-plated adhesive layer, the PI-side adhesive layer, and the PI film surface. The curing process allows the epoxy groups to continue their ring-opening reaction, and the cured network penetrates through the tin-plated and PI-side adhesive layers, thus forming a continuous interlayer bond structure composed of metal interface anchoring, organic cross-linking networks, and polymer interfacial interactions.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: The high-temperature resistant multilayer busbar electrode assembly of the present invention achieves the stability of interlayer bonding under high temperature and thermal cycling conditions by optimizing the bonding system between the tin-plated conductive base layer and the polyimide insulating film. In the tin-plated side bonding layer, the mercaptosilane coupling agent forms silicon-oxygen-tin bonds and silicon-oxygen-silicon networks on the metal surface through hydrolysis and condensation, and forms an interpenetrating continuous phase with the epoxy resin, enhancing the anchoring ability of the metal interface; in the PI side bonding layer, the heat-resistant epoxy resin, phenoxy resin, and double-terminated epoxy polydimethylsiloxane form a highly cross-linked epoxy curing network under the action of aromatic amine curing agent and imidazole accelerator, and form a continuous chemical and physical interface bond by generating hydrogen bonds and dipole interactions with the polar groups on the PI film surface through the dispersed phase structure. The microphase separation and chain segment orientation generated during the pressing and curing process of this structure regulate the interfacial stress distribution, thus limiting interlayer peeling and warpage. Therefore, the components of the present invention can maintain the interfacial bonding force and insulation performance of the conductive layer and the insulating layer during operation in a wide temperature range, improve the structural reliability and long-term stability of the laminated busbar, reduce the risk of interface defects, and improve the safety and reliability of the equipment under harsh operating conditions. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the layering of the high-temperature resistant stacked busbar electrode assembly provided in Embodiment 1 of the present invention. Detailed Implementation
[0027] The technical solutions of the present invention will be described in detail below with reference to specific embodiments and accompanying drawings. The embodiments described herein are specific implementations of the present invention, used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary, and should not be construed as limiting the implementation methods or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can employ other obvious technical solutions based on the content disclosed in the claims and specification of this application. These technical solutions include those that make any obvious substitutions and modifications to the embodiments described herein.
[0028] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone any further purification treatment.
[0029] In the embodiments, the phenoxy resin used is a commercially available solid phenoxy resin, wherein the weight-average molecular weight of the phenoxy resin is 40,000-45,000, the glass transition temperature is 84°C, and the epoxy equivalent is 7,000-15,000 g / eq. The solid phenoxy resin is a low molecular weight phenoxy resin that can be dispersed and dissolved in heat-resistant epoxy resin under heating conditions.
[0030] In the examples, the multifunctional epoxy resin was triglycidyl-m-aminophenol, CAS number 71604-74-5, with an epoxy equivalent of 105.0-115.0 g / Eq, a viscosity of 8000.0-25000.0 CPS at 25°C, and volatile matter ≤1.5%. Example 1 This embodiment provides a high-temperature resistant multilayer busbar electrode assembly and its preparation method, the preparation method specifically including the following steps: S1. A 1.5mm thick T2 copper plate is tin-plated to form a 5μm thick tin plating layer. The edges of the T2 copper plate are rounded and passivated to obtain a tin-plated conductive base layer. S2, γ-mercaptopropyltrimethoxysilane, bisphenol F epoxy resin, and ethanol are mixed to obtain a tin-plated side adhesive solution; wherein the mass ratio of γ-mercaptopropyltrimethoxysilane to bisphenol F epoxy resin is 0.5:1, the epoxy equivalent of bisphenol F epoxy resin is 170 g / eq, and the water content of ethanol is 0.1 wt.%; the mixing time is 20 min; the tin-plated side adhesive solution is coated onto the surface of the tin-plated layer and dried, the drying including a first drying section and a second drying section, the temperature of the first drying section is 70℃ and the time is 3 min, the temperature of the second drying section is 100℃ and the time is 1 min, to obtain a base-coated substrate; the thickness of the formed tin-plated side adhesive layer is 1 μm; S3, phenolic epoxy resin and phenoxy resin with a weight average molecular weight of 40,000 are mixed and heated to dissolve, obtaining a resin solution; the heating and dissolving temperature is 120℃ and the time is 60 min; then the resin solution is cooled to 90℃, and double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, m-phenylenediamine and 2-methylimidazole are added, mixed for 20 min, and then vacuum degassing is performed for 5 min to obtain PI-side adhesive; wherein, the number average molecular weight of double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane is 800; in the PI-side adhesive, the mass ratio of phenolic epoxy resin, phenoxy resin, double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, m-phenylenediamine and 2-methylimidazole is 100:5:2:20:0.3; the PI-side adhesive is coated on the tin-plated side adhesive layer surface of the undercoat substrate to obtain the coated substrate; the thickness of the formed PI-side adhesive layer is 25 μm; S4. After the corona-treated surface of the PI insulating film with a thickness of 0.05 mm comes into contact with the PI side adhesive of the coated substrate, it is pressed and cured to obtain a laminated structure. The pressing temperature is 175℃, the molding pressure is 100 kg / cm², the molding time for a single panel is 60 s, the molding time for a double panel is 120 s, and the curing conditions are 160℃ for 60 min. S5, FR-4 insulating fixing blocks are set at the ends of the laminated structure to obtain a high-temperature resistant laminated busbar electrode assembly, as shown in the layered schematic diagram. Figure 1 As shown, the electrode assembly has a multi-layer stacked structure, wherein the PI insulating film, high-temperature resistant composite adhesive layer, tin plating layer and conductive base layer can be repeatedly arranged one on top of the other.
[0031] Example 2 This embodiment provides a high-temperature resistant multilayer busbar electrode assembly and its preparation method, the preparation method specifically including the following steps: S1. A tin-plated layer with a thickness of 2.0 mm is applied to the surface of a T2 copper plate to form a tin-plated layer with a thickness of 6 μm. The edges of the T2 copper plate are rounded and passivated to obtain a tin-plated conductive base layer. S2, γ-mercaptopropyltrimethoxysilane, bisphenol A epoxy resin, and isopropanol are mixed to obtain a tin-plated side adhesive solution; wherein the mass ratio of γ-mercaptopropyltrimethoxysilane to bisphenol A epoxy resin is 1.0:1, the epoxy equivalent of bisphenol A epoxy resin is 195 g / eq, and the water content of isopropanol is 0.4 wt.%; the mixing time is 35 min; the tin-plated side adhesive solution is coated onto the surface of the tin-plated layer and dried, the drying including a first drying stage and a second drying stage, the temperature of the first drying stage is 80℃ and the time is 4.5 min, the temperature of the second drying stage is 103℃ and the time is 2.5 min, to obtain a base coating substrate; the thickness of the formed tin-plated side adhesive layer is 1.5 μm; S3, a biphenyl-type epoxy resin and a phenoxy resin with a weight-average molecular weight of 45,000 are mixed and heated to dissolve, obtaining a resin solution; the heating and dissolving temperature is 127°C and the time is 80 min; then the resin solution is cooled to 95°C, and double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, 4,4'-diaminodiphenylmethane, m-phenylenediamine and 2-ethyl-4-methylimidazole are added, mixed for 35 min, and then vacuum degassing is performed for 10 min to obtain PI-side adhesive; wherein, 4,4'- The mass ratio of diaminodiphenylmethane to m-phenylenediamine is 1:1, and the number average molecular weight of the double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane is 1200. In the PI-side adhesive, the mass ratio of biphenyl-type epoxy resin, phenoxy resin, double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, aromatic amine curing agent, and 2-ethyl-4-methylimidazolium is 100:10:4:27:0.7. The PI-side adhesive is coated onto the tin-plated adhesive layer surface of the primer substrate to obtain the coated substrate. The thickness of the formed PI-side adhesive layer is 28 μm. S4. After the roughened surface of the PI insulating film with a thickness of 0.05mm comes into contact with the PI side adhesive of the coated substrate, it is pressed and cured to obtain a laminated structure. The pressing temperature is 182℃, the molding pressure is 100kg / cm², the molding time for a single panel is 80s, the molding time for a double panel is 140s, and the curing conditions are 160℃ for 60min. S5, FR-4 insulating fixing blocks are set at the ends of the stacked structure to obtain a high-temperature resistant stacked busbar electrode assembly.
[0032] Example 3 This embodiment provides a high-temperature resistant multilayer busbar electrode assembly and its preparation method, the preparation method specifically including the following steps: S1. A tin-plated layer with a thickness of 2.5 mm is applied to the surface of a T2 copper plate to form a tin-plated layer with a thickness of 7 μm. The edges of the T2 copper plate are rounded and passivated to obtain a tin-plated conductive base layer. S2, γ-mercaptopropyltrimethoxysilane, bisphenol F epoxy resin, and acetone are mixed to obtain a tin-plated side adhesive solution; wherein the mass ratio of γ-mercaptopropyltrimethoxysilane to bisphenol F epoxy resin is 1.5:1, the epoxy equivalent of bisphenol F epoxy resin is 225 g / eq, and the water content of acetone is 0.7 wt.%; the mixing time is 45 min; the tin-plated side adhesive solution is coated onto the surface of the tin-plated layer and dried, the drying including a first drying stage and a second drying stage, the temperature of the first drying stage is 85℃ and the time is 6 min, the temperature of the second drying stage is 106℃ and the time is 4 min, to obtain a base-coated substrate; the thickness of the formed tin-plated side adhesive layer is 2.5 μm; S3, a multifunctional epoxy resin and a phenoxy resin with a weight-average molecular weight of 41,000 are mixed and heated to dissolve, resulting in a resin solution; the heating and dissolving temperature is 133°C and the time is 100 min; then the resin solution is cooled to 93°C, and double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, 4,4'-diaminodiphenylmethane and 2-phenylimidazole are added, mixed for 45 min and then vacuum degassing is performed for 15 min to obtain PI side adhesive; The number average molecular weight of the double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane is 1600. In the PI-side adhesive, the mass ratio of multifunctional epoxy resin, phenoxy resin, double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, 4,4'-diaminodiphenylmethane, and 2-phenylimidazole is 100:15:6:34:1.1. The PI-side adhesive is coated onto the tin-plated adhesive layer surface of the base-coated substrate to obtain the coated substrate. The thickness of the formed PI-side adhesive layer is 31 μm. S4. After the corona-treated surface of a 0.05mm thick PI insulating film comes into contact with the PI side adhesive of the coated substrate, it is pressed and cured to obtain a laminated structure. The pressing temperature is 188℃, the molding pressure is 100kg / cm², the molding time for a single panel is 100s, the molding time for a double panel is 160s, and the curing conditions are 160℃ for 60min. S5, FR-4 insulating fixing blocks are set at the ends of the stacked structure to obtain a high-temperature resistant stacked busbar electrode assembly.
[0033] Example 4 This embodiment provides a high-temperature resistant multilayer busbar electrode assembly and its preparation method, the preparation method specifically including the following steps: S1. A 3.0 mm thick T2 copper plate is subjected to surface tin plating to form an 8 μm thick tin plating layer. The edges of the T2 copper plate are rounded and passivated to obtain a tin-plated conductive base layer. S2, γ-mercaptopropyltrimethoxysilane, bisphenol A epoxy resin, and ethanol are mixed to obtain a tin-plated side adhesive solution; wherein the mass ratio of γ-mercaptopropyltrimethoxysilane to bisphenol A epoxy resin is 2.0:1, the epoxy equivalent of bisphenol A epoxy resin is 250 g / eq, and the water content of ethanol is 1.0 wt.%; the mixing time is 60 min; the tin-plated side adhesive solution is coated onto the surface of the tin-plated layer and dried, the drying including a first drying stage and a second drying stage, the temperature of the first drying stage is 90℃ and the time is 8 min, the temperature of the second drying stage is 110℃ and the time is 5 min, to obtain a base-coated substrate; the thickness of the formed tin-plated side adhesive layer is 3 μm; S3, phenolic epoxy resin and phenoxy resin with a weight average molecular weight of 43,000 are mixed and heated to dissolve to obtain a resin solution; the heating and dissolving temperature is 140℃ and the time is 120min; then the resin solution is cooled to 92℃, and double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, 4,4'-diaminodiphenylmethane and 2-ethyl-4-methylimidazolium are added, mixed for 60min and then vacuum degassing is performed for 20min to obtain PI side adhesive; The number average molecular weight of the double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane is 2000; in the PI-side adhesive, the mass ratio of phenolic epoxy resin, phenoxy resin, double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, 4,4'-diaminodiphenylmethane and 2-ethyl-4-methylimidazolium is 100:20:8:40:1.5; the PI-side adhesive is coated onto the tin-plated adhesive layer surface of the base-coated substrate to obtain the coated substrate; the thickness of the formed PI-side adhesive layer is 35 μm; S4. After the roughened surface of the PI insulating film with a thickness of 0.05mm comes into contact with the PI side adhesive of the coated substrate, it is pressed and cured to obtain a laminated structure. The pressing temperature is 195℃, the molding pressure is 100kg / cm², the molding time for a single panel is 120s, the molding time for a double panel is 180s, and the curing conditions are 160℃ for 60min. S5, FR-4 insulating fixing blocks are set at the ends of the stacked structure to obtain a high-temperature resistant stacked busbar electrode assembly.
[0034] Comparative Example 1 This comparative example provides a high-temperature resistant laminated busbar electrode assembly and its preparation method. The difference between this and Example 1 is that no tin-plated side adhesive layer is prepared. Instead, the PI side adhesive is directly coated onto the surface of the tin-plated layer. Other process parameters and operating conditions are exactly the same as in Example 1.
[0035] Comparative Example 2 This comparative example provides a high-temperature resistant laminated busbar electrode assembly and its preparation method. The difference between this example and Example 1 is that γ-mercaptopropyltrimethoxysilane is not added to the tin-plating side adhesive solution. Instead, only bisphenol F type epoxy resin and ethanol are used to prepare the tin-plating side adhesive solution. Other process parameters and operating conditions are exactly the same as in Example 1.
[0036] Comparative Example 3 This comparative example provides a high-temperature resistant laminated busbar electrode assembly and its preparation method. The difference between this example and Example 1 is that no double-ended epoxypropoxypropyl-terminated polydimethylsiloxane is added to the PI side adhesive. Other process parameters and operating conditions are exactly the same as in Example 1.
[0037] Comparative Example 4 This comparative example provides a high-temperature resistant laminated busbar electrode assembly and its preparation method. The difference between this example and Example 1 is that no phenyloxy resin is added to the PI side adhesive, while the other process parameters and operating conditions are exactly the same as in Example 1.
[0038] Comparative Example 5 This comparative example provides a high-temperature resistant laminated busbar electrode assembly and its preparation method. The difference between this and Example 1 is that the side of the PI insulating film facing the PI side adhesive is not roughened or corona treated. Other process parameters and operating conditions are exactly the same as in Example 1.
[0039] Test method: The high-temperature resistant laminated busbar electrode assemblies prepared in Examples 1-4 and Comparative Examples 1-5 were cut into test samples, with 3 samples in each group. Before testing, all samples were placed in an environment of 23±2℃ and 50±5% relative humidity for 24 hours to equilibrate.
[0040] Initial peel strength test: The sample was cut into peel test pieces with a width of 25 mm and a length of 150 mm. A pre-peel length of 30 mm was applied to the end of the PI insulating film to form a clamping end. A 180° peel test was performed using an electronic universal testing machine. The clamp spacing was set to 50 mm, the peel speed was set to 50 mm / min, and the test environment was 23±2℃ and relative humidity 50±5%. The average peel force during the stable peeling stage was recorded, and the peel strength was calculated by dividing the average peel force by the sample width, in N / mm. Three samples were tested in each group, and the average value was taken as the initial peel strength.
[0041] Peel strength retention rate test after heat aging: Samples from the same batch that have not undergone the initial peel strength test are placed in a forced-air drying oven and kept at 150℃ for 168 hours. After heat aging, the samples are removed and placed in an environment of 23±2℃ and 50±5% relative humidity for 2 hours to equilibrate. Then, the peel strength after heat aging is measured according to the initial peel strength test method. The peel strength retention rate after heat aging is calculated by the following formula: Peel strength retention rate after heat aging = Peel strength after heat aging / Initial peel strength × 100%.
[0042] Peel strength retention rate test after thermal cycling: Samples from the same batch were placed in a thermal shock test chamber for thermal cycling treatment. The thermal cycling conditions were as follows: low temperature section -40℃, held for 30 min; temperature rise to 150℃, heating rate 5℃ / min; high temperature section 150℃, held for 30 min; temperature drop to -40℃, cooling rate 5℃ / min; the above process constituted one cycle, and a total of 100 cycles were performed. After the cycle, the samples were placed in an environment of 23±2℃ and relative humidity 50±5% for 2 h to equilibrate, and then the peel strength after thermal cycling was measured according to the initial peel strength test method. The peel strength retention rate after thermal cycling was calculated by the following formula: Peel strength retention rate after thermal cycling = Peel strength after thermal cycling / Initial peel strength × 100%.
[0043] Insulation resistance test: The insulation resistance of the samples was tested using a high-resistance meter. Before testing, the samples were placed in an environment of 23±2℃ and 50±5% relative humidity for 24 hours to equilibrate. During testing, the positive test terminal of the high-resistance meter was connected to the conductive substrate, and the negative test terminal was connected to the test electrode on the outside of the sample. The test voltage was set to DC1000V, and the voltage application time was 60s. The stable insulation resistance value was read. Three samples were tested in each group, and the average value was taken as the insulation resistance.
[0044] Warpage Measurement: After equilibration for 2 hours in an environment of 23±2℃ and 50±5% relative humidity, the sample was placed on a granite testing platform, allowing it to lie flat naturally without external pressure. A laser displacement sensor was used to scan the sample along its length and width at 10mm intervals, recording the height of each measuring point on the sample surface. Warpage was calculated as the difference between the highest and lowest measuring point heights, in mm. The warpage of the initial sample, the sample after 168 hours of heat aging at 150℃, and the sample after 100 cycles of thermal cycling from -40℃ to 150℃ were all measured using the above method. Three samples were tested in each group, and the average value was taken as the test result.
[0045] The test results are shown in Table 1.
[0046] Table 1 Test results of Examples 1-4 and Comparative Examples 1-5 As shown in Table 1, compared to Example 1, Comparative Example 1 had the same initial peel strength, but lower heat aging peel strength retention rate, lower thermal cycling peel strength retention rate, lower insulation resistance, and increased warpage. Comparative Example 2 had an increased initial peel strength, lower heat aging peel strength retention rate, lower thermal cycling peel strength retention rate, lower insulation resistance, and increased warpage. Comparative Example 3 had an increased initial peel strength, lower heat aging peel strength retention rate, lower thermal cycling peel strength retention rate, lower insulation resistance, and increased warpage. Comparative Example 4 had an increased initial peel strength, lower heat aging peel strength retention rate, lower thermal cycling peel strength retention rate, lower insulation resistance, and increased warpage. Comparative Example 5 had an increased initial peel strength, lower heat aging peel strength retention rate, lower thermal cycling peel strength retention rate, lower insulation resistance, and increased warpage.
[0047] This is because Comparative Example 1 did not have a tin-plated adhesive layer, and the PI-side adhesive was in direct contact with the tin-plated layer. In the initial state, it could still form an adhesive through resin wetting, so the initial peel strength was the same as that of Example 1. However, the tin-plated layer side lacked the transition adhesive structure formed by γ-mercaptopropyltrimethoxysilane and epoxy resin. After thermal aging and thermal cycling, the interfacial bonding stability of the tin-plated layer side decreased, resulting in a decrease in peel strength retention. After the increase in interfacial defects, the insulation resistance decreased, and the uneven release of interlayer thermal stress increased the warpage. In Comparative Example 2, no γ-mercaptopropyltrimethoxysilane was added to the tin-plated side adhesive solution. Only epoxy resin was used to form the tin-plated side adhesive layer. In the initial state, the pure epoxy resin layer did not contain siloxane rigid domains. The uniformity and room temperature compliance of the layer were better than those of the tin-plated side adhesive layer containing silane condensation structure, thus increasing the initial peel strength. However, the tin-plated layer lacked the interfacial connection formed by silane hydrolysis condensation and the interfacial effect of mercapto groups on the tin surface. After thermal aging and thermal cycling, the interfacial bonding stability of the metal side decreased, resulting in a decrease in peel strength retention, a decrease in insulation resistance, and an increase in warpage.
[0048] In Comparative Example 3, the PI-side adhesive did not contain double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane. This increased the proportion of rigid epoxy-cured networks in the PI-side adhesive layer, leading to higher initial peel strength. However, the lack of polydimethylsiloxane segments in the cured network reduced the buffering capacity against thermal deformation differences between the conductive substrate and the PI insulating film during thermal cycling, resulting in lower peel strength retention after thermal cycling. Intralayer stress concentration further reduced insulation resistance and increased warpage. In Comparative Example 4, the PI-side adhesive did not contain phenoxy resin. This increased the proportion of epoxy-cured networks in the PI-side adhesive layer, leading to higher initial peel strength. However, the lack of linear polyhydroxy ether segments to regulate the film continuity and interfacial toughness of the thin adhesive layer resulted in increased local stress concentration during thermal aging and thermal cycling, leading to lower peel strength retention, lower insulation resistance, and increased warpage. In Comparative Example 5, the PI insulating film was not roughened or corona treated. Under the initial pressing state, the PI side adhesive could still form an adhesive through resin wetting. However, the PI surface lacked micro-intercalation structure and oxygen-containing polar groups. After thermal aging and thermal cycling, the bonding stability of the PI side interface decreased, resulting in a decrease in peel strength retention, a decrease in insulation resistance, and an increase in warpage.
[0049] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A high-temperature resistant laminated busbar electrode assembly, characterized in that, Includes conductive base layer, tin plating layer, high temperature resistant composite adhesive layer, PI insulating film and FR-4 insulating fixing block; The tin plating layer is disposed on the surface of the conductive substrate; the high-temperature resistant composite adhesive layer is disposed between the tin plating layer and the PI insulating film; The high-temperature resistant composite adhesive layer includes a tin-plated side adhesive layer in contact with the tin-plated layer and a PI-side adhesive layer in contact with the PI insulating film; the tin-plated side adhesive layer includes γ-mercaptopropyltrimethoxysilane and epoxy resin. The PI-side adhesive layer includes heat-resistant epoxy resin, phenoxy resin, double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, aromatic amine curing agent and imidazole curing accelerator. The side of the PI insulating film facing the high-temperature resistant composite adhesive layer is a roughened surface or a corona-treated surface. The FR-4 insulating fixing block is disposed at the end of the stacked structure formed by the conductive base layer, the tin-plated layer, the high-temperature resistant composite adhesive layer and the PI insulating film.
2. The high-temperature resistant laminated busbar electrode assembly according to claim 1, characterized in that, The conductive base layer is a T2 copper plate with a thickness of 1.5-3.0 mm; the tin plating layer has a thickness of 5-8 μm; and the edges of the conductive base layer are provided with a rounded corner passivation structure.
3. The high-temperature resistant laminated busbar electrode assembly according to claim 1, characterized in that, The thickness of the PI insulating film is 0.05 mm.
4. The high-temperature resistant laminated busbar electrode assembly according to claim 1, characterized in that, The thickness of the tin-plated side adhesive layer is 1-3 μm, and the thickness of the PI side adhesive layer is 25-35 μm.
5. The high-temperature resistant laminated busbar electrode assembly according to claim 1, characterized in that, The epoxy resin is one or both of bisphenol A type epoxy resin and bisphenol F type epoxy resin, and the epoxy equivalent of the epoxy resin is 170-250 g / eq.
6. The high-temperature resistant laminated busbar electrode assembly according to claim 1, characterized in that, In the tin-plated adhesive layer, the mass ratio of γ-mercaptopropyltrimethoxysilane to the epoxy resin is (0.5-2):
1.
7. The high-temperature resistant laminated busbar electrode assembly according to claim 1, characterized in that, In the PI side adhesive layer, the mass ratio of the heat-resistant epoxy resin, phenoxy resin, double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, aromatic amine curing agent and imidazole curing accelerator is 100:(5-20):(2-8):(20-40):(0.3-1.5).
8. The high-temperature resistant laminated busbar electrode assembly according to claim 1, characterized in that, The heat-resistant epoxy resin is one or more of phenolic epoxy resin, biphenyl epoxy resin, and multifunctional epoxy resin; the weight-average molecular weight of the phenoxy resin is 40,000-45,000; the number-average molecular weight of the double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane is 800-2,000; the aromatic amine curing agent is one or two of 4,4'-diaminodiphenylmethane and m-phenylenediamine; and the imidazole curing accelerator is one or more of 2-ethyl-4-methylimidazolium, 2-methylimidazolium, and 2-phenylimidazolium.
9. A high-temperature resistant laminated busbar electrode assembly according to claim 1, characterized in that, The PI side adhesive layer further includes sheet-like insulating filler, which is one or more of sheet-like boron nitride, sericite, and sheet-like talc; the mass ratio of the heat-resistant epoxy resin to the sheet-like insulating filler is 100:(1-8), the average sheet diameter of the sheet-like insulating filler is not greater than 5μm, the maximum sheet diameter is not greater than 8μm, and the aspect ratio is not less than 10.
10. A method for preparing a high-temperature resistant laminated busbar electrode assembly as described in any one of claims 1-9, characterized in that, Includes the following steps: S1, the conductive substrate is subjected to surface tin plating to form a tin plating layer, and the edges of the conductive substrate are rounded and passivated. S2, mix γ-mercaptopropyltrimethoxysilane, epoxy resin and organic solvent to obtain tin-plated side adhesive liquid, coat the tin-plated side adhesive liquid onto the surface of the tin-plated layer and dry it to obtain a base coating substrate; S3, heat-resistant epoxy resin and phenoxy resin are mixed and heated to dissolve. After cooling, double-ended epoxypropoxypropyl-terminated polydimethylsiloxane, aromatic amine curing agent and imidazole curing accelerator are added. After mixing, PI side adhesive is obtained. The PI side adhesive is coated on the tin-plated side adhesive layer surface of the base coating substrate to obtain the adhesive-coated substrate. S4, after the roughened surface or corona-treated surface of the PI insulating film comes into contact with the PI side adhesive of the coated substrate, it is pressed and cured to obtain a laminated structure. S5, FR-4 insulating fixing blocks are provided at the ends of the stacked structure to obtain a high-temperature resistant stacked busbar electrode assembly.
11. The method for preparing a high-temperature resistant laminated busbar electrode assembly according to claim 10, characterized in that, In S2, the organic solvent is one or more of ethanol, isopropanol, and acetone, and the water content of the organic solvent is 0.1-1.0 wt.%; the mixing time is 20-60 min; the drying includes a first drying section and a second drying section, the temperature of the first drying section is 70-90℃ and the time is 3-8 min, and the temperature of the second drying section is 100-110℃ and the time is 1-5 min.
12. The method for preparing a high-temperature resistant laminated busbar electrode assembly according to claim 10, characterized in that, In S3, the temperature at which the heat-resistant epoxy resin and the phenoxy resin are mixed and heated to dissolve is 120-140℃ for 60-120 minutes; the temperature after cooling is 90-95℃; the mixing time after adding the double-terminated epoxypropoxypropyl-terminated polydimethylsiloxane, aromatic amine curing agent and imidazole curing accelerator is 20-60 minutes; after mixing, vacuum degassing is performed for 5-20 minutes.
13. The method for preparing a high-temperature resistant laminated busbar electrode assembly according to claim 10, characterized in that, In step S4, the pressing temperature is 175-195℃, and the molding pressure is 100 kg / cm². 2 The molding time for single-sided panels is 60-120s, and the molding time for double-sided panels is 120-180s. The curing conditions are 160℃ for 60min.
Citation Information
Patent Citations
Adhesive capable of reducing stress and improving temperature resistance and preparation method thereof
CN114231230A
Composite current collector double-sided coating film and preparation method thereof
CN122277967A